Ar-B (Augmented Reality and Brille) Module Innovation of Learning Media in the Fulfillment of Human Rights Field of Education for Visually Impaired Person - Oviensy, Vegia (Badan Strategi Kebijakan Hukum, 2022)
The development of the Ar-B (Augmented Reality and Braille) TikTok-based Learning Media Innovation in Indonesia addresses a critical human rights issue especially on ensuring equal access to education for individuals with disabilities, particularly those with visual impairments. Despite there being over 3 million visually impaired individuals in Indonesia, only a fraction of media content is accessible to them. This stark inequality violates the fundamental human rights principles of non-discrimination and equal access to education, as outlined in international agreements such as the Universal Declaration of Human Rights and the Convention on the Rights of Persons with Disabilities. During the COVID-19 pandemic, when traditional educational avenues were disrupted, 99% of students turned to social media for learning, highlighting the urgency to make digital platforms inclusive. TikTok emerged as a predominant medium, with a significant proportion of students using it extensively. The Ar-B innovation leverages technology to bridge this accessibility gap by integrating Augmented Reality and Braille, thus enabling both visually impaired and non-impaired students to access educational content effectively on TikTok. Through the Research and Development (R&D) process and rigorous validation, the Ar-B Module has demonstrated a 92% validity rate and shown to enhance student learning outcomes. By ensuring that educational tools are inclusive and accessible, this innovation not only supports the educational rights of disabled individuals but also contributes to broader human rights goals of equity and inclusivity in education. It exemplifies Indonesia's commitment to fulfilling its obligations under international human rights frameworks by promoting inclusive education through innovative technological solutions.